2011
DOI: 10.1371/journal.pone.0023752
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB–Dependent Epithelial to Mesenchymal Transition Induced by HIF-1α Activation in Pancreatic Cancer Cells under Hypoxic Conditions

Abstract: BackgroundEpithelial to mesenchymal transition (EMT) induced by hypoxia is one of the critical causes of treatment failure in different types of human cancers. NF-κB is closely involved in the progression of EMT. Compared with HIF-1α, the correlation between NF-κB and EMT during hypoxia has been less studied, and although the phenomenon was observed in the past, the molecular mechanisms involved remained unclear.Methodology/Principal FindingsHere, we report that hypoxia or overexpression of hypoxia-inducible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…GLI1 knockdown by RNA interference restrains cell invasion and EMT in HCC [31]. Moreover, some studies recently showed that numerous molecular signaling pathways, containing Hh pathway [32], could be activated under hypoxia conditions [33, 34]. However, the function of Hh pathway involved in the hypoxia-driven EMT and metastasis of HCC cells together with its relation with HIF-1α-induced ROS remain unclarified.…”
Section: Introductionmentioning
confidence: 99%
“…GLI1 knockdown by RNA interference restrains cell invasion and EMT in HCC [31]. Moreover, some studies recently showed that numerous molecular signaling pathways, containing Hh pathway [32], could be activated under hypoxia conditions [33, 34]. However, the function of Hh pathway involved in the hypoxia-driven EMT and metastasis of HCC cells together with its relation with HIF-1α-induced ROS remain unclarified.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology has been described previously (41). In brief, BxPC-3 cells were seeded in 6-well plates and incubated for 24 hours at 37 C. The cells were then transfected with NF-kB p65 cDNA, control empty vector (pcDNA3.0), NF-kB p65 siRNA and control siRNA, respectively, using Lipofectamine 2000 (Invitrogen).…”
Section: Plasmids and Transfectionsmentioning
confidence: 99%
“…It has be further investigated to what extent HIF--1α and PDGF--A are coexpressed in pancreatic cancer [88]. Recent data show a correlation between hypoxic environment, induced HIF--1α expression and pancreatic cancer cells resistance to gemcitabine [89]; furthermore HIF--1α overexpression seems promote EMT and facilitate invasiveness of pancreatic cancer cells [90,91].…”
Section: Novel Molecular Targets: Hif and Angiogenesismentioning
confidence: 99%